Financial frictions and firm informality - Franjo, Luis,Pouokam, Nathalie,Turino, Francesco (International Monetary Fund, 2020)
In this paper we build a model of occupational choice with informal production and progressive income taxation. We calibrate the model to the Brazilian economy to evaluate the impact of removing financial frictions on informality. We find that financial deepening leads to a drop in the size of the informal sector (from 37 percent to 22 percent of official GDP), to an increase in measured TFP (by 4 percent), to an increase in official GDP (by 27 percent), to a decrease in tax evasion (by 17 percent) and to an increase in fiscal revenues (by 15 percent). When assessing the response of this policy at different levels of financial development, we find a non-linear relationship between the credit-to-GDP ratio on the one hand, and either the size of the informal economy, or GDP per capita on the other hand. We test these features with cross-country data and find evidence in favor of both types of non-linearity. We also investigate changes in the income tax progressitivity as an alternative policy and find it to be more effective in countries with a medium to high level of financial markets development
10.5089/9781513557809.001
Keywords: Graue Literatur; Informelle Wirtschaft; Allgemeines Gleichgewicht; Erwerbsverlauf; Steuermoral; Bruttoinlandsprodukt; Produktivitätsentwicklung; Kreditmarkt; Business and Economics; Money and Monetary Policy; Taxation; Economics: General; Economic Theory; Macroeconomics: Consumption; Saving; Wealth; Investment; Capital; Intangible Capital; Capacity; Informal Economy; Underground Econom; Financial Markets and the Macroeconomy; Tax Evasion and Avoidance; Economic Development: General; Economic Growth and Aggregate Productivity: General; Labor Demand; Financial Economics; Monetary Policy; Central Banking; and the Supply of Money and Credit: General; Labour; income economics; Public finance & taxation; Economic theory & philosophy; Monetary economics; Economics of specific sectors; Self-employment; Financial frictions; Informal economy; Labor; Economic theory; Revenue administration; Money; Economic sectors; Self-employed; Tax evasion; Economic forecasting; Credit; Informal sector; Economics; informality; financial frictions; taxation; entrepreneurship; productivity; misallocation